A Postal Screener for Pain and Need for Treatment in Older Persons in Primary Care. Issue 10 (3rd October 2014) - de Waal, Margot W. M.; den Elzen, Wendy P. J.; Achterberg, Wilco P.; Gussekloo, Jacobijn; Blom, Jeanet W.
<x xml:space="preserve">Abstract</x> Objectives To test the Pain intensity, Enjoyment in life, General activity questionnaire (PEG) as a postal screener for pain in older persons. Design Population‐based survey. Postal screening questionnaires followed by an interview of a sample of participants. Setting Family practices. Participants Persons aged 75 and older (N = 243; 95 interviewed). Measurements Screening included the PEG, a three‐item abbreviated version of the Brief Pain Inventory (BPI), plus an additional question on treatment need. Pain severity and related interference was assessed (BPI) during the interview, as was the current (need for) pain treatment. Results The median PEG score of the 243 persons participating in the screening (response 76%) was 2.0 (interquartile range 0–4.7). Seventy‐nine (35%) had moderate to severe pain (PEG score ≥4), of whom 56% reported current pain treatment and 15% stated that they might ask for help. For a PEG score cutoff of 4 or greater, sensitivity was 0.81 and specificity was 0.78 to find scores of 4 or greater on one or both BPI subscales during the interview. For the question on need for treatment, replies on the screener and the interview were not always consistent. Of the 43 interviewed participants with a PEG score of 4 or greater, 60% received treatment. Of the 17 without current pain treatment, 10 still reported pain, three of whom said that they might ask for help. Conclusion The PEG can be used as a postal screener to detect the presence of pain in older persons, but treatment needs cannot be established using the PEG alone or in combination with a simple additional question.